KONDISI SOSIAL EKONOMI PETERNAK JANGKRIK (GRYULLUS MITRACTUDI KELURAHAN KALUMBUK KECAMATAN KURANJI KOTA PADANG - Helman, Nofri; Rianto, Slamet; Nefelinda, Nefelinda (Pendidikan Geografi, 2013)
This study aimed to obtain the data, process, analyze and discuss the socio-economic conditions of farmers crickets (Gryllus mitratus) in the Village District Kalumbuk Kuranji city of Padang views: 1) Education breeder crickets (Gryllus mitratus), 2) Revenue breeder crickets (Gryllus mitratus ), 3) social relationships breeder crickets (Gryllus mitratus), and 4) Facilities and infrastructure breeding crickets (Gryllus mitratus). This study considered the descriptive research. Population of this research is all the family head breeder crickets (Gryllus mitratus) in the Village kalumbuk. Respondent sampling done with total sampling technique, which amounted to 45 respondents. The research data was collected through questionnaires. Data were analyzed using descriptive analysis techniques and the percentage formula. The results of this study as follows: 1) Education in Sub Kalumbuk cricket breeder is generally completed high school (44.44%), 2) Average income per capita in Sub Kalumbuk cricket breeder is high, where there is a 51.85% farmers who have income between Rp 4,000,000 - Rp 5,000,000 a month, 3) social relations knick cricket with the family (father, mother, and children), neighbors, and buyers are very good cricket but cricket relations with fellow rancher unfavorable because there 14.81% of respondents who have a poor relationship with a fellow breeder crickets, 4) facilities and infrastructure in the Village Kalumbuk breeding crickets good (38.49%), but still there are 18.52% of the respondents who had the condition of sewer water and waste bad. Cricket breeder should further enhance knowledge about cricket, cricket farm to develop, maintain good relations with fellow rancher crickets and maintain the condition of the farm infrastructure crickets.